Morpho-agronomic and genetic evaluation of long day garlic (Allium sativum) - KAUSHAL, ANUBHA; MEHTA, DEVINDER K; BHARDWAJ, RAMESH KUMAR; DOGRA, RAJESH K; GUPTA, MEENU; KHAR, ANIL; PATHANIA, RAHUL; YADAV, NITIN (The Indian Journal of Agricultural Sciences, 2025)
In India, productivity of garlic (Allium sativum L.) is low due to non-availability of high yielding varieties for a particular province/state. In India, Himachal Pradesh is the major garlic producing state amongst the various hilly regions. In Himachal Pradesh, districts like Sirmour, Solan, Kullu, Mandi and Kangra are main garlic producer and meet the demand of garlic seed of whole state, but majority of varieties are low yielding. The present study was carried out during 2022–23 and 2023–24 at Dr. Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to evaluate morphological and horticultural traits of garlic in mid-hill environments of Himachal Pradesh. Thirty-five genotypes of garlic including cultivar Solan Selection as check were evaluated for yield and yield contributing characters based on DUS guidelines notified by Protection of Plant Varieties and Farmer’s Right Act (PPV&FRA). The experiment was laid out in a randomized complete block design (RCBD) with three replications. The results revealed that LGC–20, LGC–2, and LGC–22 performed better in terms of yield with 52.27%, 48.51% and 45.78% increase over check variety, Solan Selection, respectively. Furthermore, the DUS traits like leaf, stem, pseudo-stem, bulb, clove weight, clove size, bulb yield, maturity and incidence of rust, were also exhibited wide variation and found helpful in enhancing yield of garlic. Clustering analysis differentiated all the genotypes into four major clusters based on various traits studied. The Principal Component Analysis (PCA) represented a similar grouping of the genotypes which helps in the assessment of diversity in the multivariate analysis and indicated morphological variation of the germplasm under study. Therefore, based on present investigation, it is recommended that high yielding genotypes LGC-20 (259.45 q/ha), LGC-2 (240.25 q/ha) and LGC-22 (239.69 q/ha) with improved productivity and variable morphological traits were found promising genotypes and can be recommended for commercial cultivation to enhance the profitability of stake holders.